Proteomics today : protein assessment and biomarkers using mass spectrometry, 2D electrophoresis, and microarray technology - Hamdan, Mahmoud; Righetti, Pier Giorgio (Wiley-Interscience, 2005)
The last few years have seen an unprecedented drive toward the application of proteomics to resolving challenging biomedical and biochemical tasks. Separation techniques combined with modern mass spectrometry are playing a central role in this drive. This book discusses the increasingly important role of mass spectrometry in proteomic research, and emphasizes recent advances in the existing technology and describes the advantages and pitfalls as well. * Provides a scientifically valid method for analyzing the approximatey 500,000 proteins that are encoded in the human genome * Explains the hows and whys of using mass spectrometry in proteomic analysis * Brings together the latest approaches combining separation techniques and mass spectrometry and their application in proteome analysis * Comments on future challenges and how they may be addressed * Includes sections on troubleshooting
Wiley-Interscience series on mass spectrometry
Keywords: elektroforéza; biologie; Electrophoresis; chemie, klinická chemie; proteiny; Proteins; SPEKTROMETRIE HMOTOVÁ - BOMBARDOVÁNÍ RYCHLÝMI ATOMY